Exploring the English Needs of Students of International Relations Department at an Indonesian University Context - Saputro, Teguh Hadi; Hima, Aninda Nidhommil (English Education: Jurnal Tadris Bahasa Inggris, 2018)
This study on the needs analysis aimed at understanding the actual and immediate English needs of International Relations department (IRD) students at an Indonesia university. The adapted version of Ekici's (2003) and Mazdayasna and Tahririan's (2008) questionnaire was used as the main instrument of the study to explore the perception of 340 IRD students about their needs in learning English in the framework of English for Specific Purposes (ESP). These students consisted of sophomores, juniors and seniors. Their responses were analyzed statistically by calculating the mean, standard deviation and percentage of the response. This study also employed interviews as the instrument to further investigate the results of the questionnaire. Head of IRD, IRD lecturers and ESP lecturers were involved in the interview. The results revealed the list of perceived needs that were classified into three categories, namely strongly-perceived, less strongly-perceived and irrelevant needs. From the list, it could be learned that most of the IRD students’ needs were associated with an expectation of being able to understand and use English during their undergraduate study. In other words, the ESP program in the particular university has to be in the form of EAP or ESAP so as to facilitate the students’ needs. This recommendation had also been acknowledged and approved by the head of IRD and IRD lecturers as the content-related experts and the ESP lecturers as the language experts although a slight different view point about this matter is also identified.